Mathematical analysis of a HIV model with frequency dependence and viral diversity - Shingo Iwami; Shinji Nakaoka; Yasuhiro Takeuchi (Mathematical Biosciences and Engineering)
We consider the effect of viral diversity on the human immune sys-tem with the frequency dependent proliferation rate of CTLs and the elimina-tion rate of infected cells by CTLs. The model has very complex mathematicalstructures such as limit cycle, quasi-periodic attractors, chaotic attractors, andso on. To understand the complexity we investigate the global behavior of themodel and demonstrate the existence and stability conditions of the equilibria.Further we give some theoretical considerations obtained by our mathematicalmodel to HIV infection.